Algernon Charles Swinburne correspondence - Swinburne, Algernon Charles, 1837-1909.
ALS (1868 December 5) from Swinburne to Ulrica Fenwick and photocopy of an ALS (New Year's Day, no year) to a Mr. Brown.
In part, negative photocopy produced from an original in the possession of Charles C. Hart.
English poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fenwick, Ulrica -- Correspondence; Poets, English -- 19th century -- Correspondence; Poets